Case Report: Pemphigoid Nodularis—Five Patients With Many Years of Follow-Up and Review of the Literature - Szymanski, Konrad; Adaszewska, Alicja; Jakubowska, Beata; Kowalewski, Cezary; Pietrzyk, Ewelina; Wozniak, Katarzyna (Frontiers in Immunology, 2022)
Pemphigoid nodularis is a rare form of pemphigoid that joins clinical picture of prurigo nodularis and immunological features of bullous pemphigoid, which is therapeutically challenging. Here, we analyze five female patients with long lasting course of nodular pemphigoid in term of clinical and immunological characteristics and therapy. All the patients fulfilled clinical and immunological criteria of nodular pemphigoid. We applied numerous techniques allowing the proper diagnosis: direct and indirect immunofluorescence, salt split skin, ELISA, BIOCHIP, Fluorescence Overlay Antigen Mapping using Laser Scanning Confocal Microscopy. Our study showed that 4 of 5 patients fulfilled clinical and immunological criteria of nodular bullous pemphigoid. Two patients of 4 presented exclusively nodular lesions, in other two patients blisters and erythematous lesions preceded prurigo-like lesions by a few years. Remaining one patient had clinical and immunological criteria of nodular mucous membrane pemphigoid, presenting oral erosions, scarring conjunctivitis and numerous disseminated nodules on the skin. All the patients were treated with multiple medicines, however the best control of the disease in them was observed using clobetasol propionate on the entire body plus antidepressants. Pemphigoid nodularis mainly occurs in elderly women. In cases with coexisting psychological problems clobetasol propionate plus antidepressants should be considered as first.